Sports officials in home advantage phenomenon: A new framework - DOSSEVILLE, Fabrice; EDOH, KOFFI PIERROT; MOLINARO, Corinne (My University, 2015)
The home advantage is one of the best-established and documented phenomenon in sports settings. Conceptual frameworks do not involve, or little, sports official. Nevertheless, we assume that this decision-maker play a determinant role. Thus, the main objective of this paper was to propose a conceptual framework of home advantage including the sports officials and to guide future research on the influence of sports officials on the home advantage phenomenon. Situational, contextual, individual and ethical/economic dimensions compose this new framework.
Keywords: sport officiating; home advantage; decision-making